Kemampuan Filter Rokok Non-Pakai Sebagai Adsorben Dalam Mengurangi Gas Emisi CO Dan HC - Mukhammad Rifki Hendianto; Novirina Hendrasarie (Fakultas Teknik, 2020)
Air is the most important element for life. However, the air we breathe now tends to be dirty and not good for health. Air pollution occurs due to transportation activities. Cigarette filter manufacturers produce cigarette filters that are not suitable for use because they do not meet standards. This research utilizes an unused cigarette filter which can only become waste that was difficult to decompose by nature. This study aimed to assess the ability of unused cigarette filters to reduce gas emissions, carbon monoxide (CO), and hydrogen carbon (HC). This unused cigarette filter, known as an adsorbent, was made of highly absorbed cellulose acetate. These cigarette filter adsorbent has been studied on motorcycle exhausts since the 2000s. By modifying the type of cigarette filter, namely the ordinary cigarette filter in which carbon is added. The results showed that the unused cigarette filter was able to become an adsorbent for pollutants in the air, especially CO and HC. The type of cigarette filter that uses additional carbon has been shown to reduce CO and HC concentrations by 60% and 57.5%, respectively, than conventional cigarette filters.